The Evaluation of Public Relations Management’s Efforts from the Perspective of the Internal Public in Hotels "Case Study: Afamia Hotel" - Ibrahim, Nour (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The research problem has focused on the role of public relations management in creating and enhancing the internal public’s confidence with the hotel, and improving the hotel mental image, that the staff has. The researcher used the case study method and depended on descriptive approach in the research community (Afamia Hotel). In addition to the Trilogy Approach (survey- interview- observation) to collect primary data, Then the researcher analyzed the survey results by the Statistical Package for the Social Sciences (SPSS). The research concluded the following findings: Public relations management follows the top management directly. The number of public relations employees is not enough to do their jobs efficiently. All the Public Relations employees have university degrees, but they are not related to the specialization of the PR. Lack of communication devices in the PR management. The budget is not enough, and there is a lack of human and material resources. The PR management is oriented towards the external audiences alone. A large percentage of the hotel employees is unaware of tasks and functions of the public relations management. PR management does not survey the internal public opinions and they do not take advantage of the good electronic infrastructure that the hotel has. تقييم جهود إدارة العلاقات العامة من وجهة نظر الجمهور الداخلي للمنشآت الفندقية )دراسة حالة فندق أفاميا في محافظة اللاذقية( هدفت الدراسة إلى التعرف على الدور الذي تقوم به إدارة العلاقات العامة بهدف خلق وتعزيز الثقة مع الجمهور الداخلي للمنشأة الفندقية المدروسة، وتحسين الصورة الذهنية للمنشأة لدى العاملين فيها. وقد اتبعت الباحثة أسلوب دراسة الحالة، حيث استخدمت لذلك المنهج الوصفي، وتمّ تصميم وتوزيع استبانة على العاملين في المنشأة الفندقية المدروسة، كما تمّت دراسة وتحليل البيانات باستخدام برنامج spss وقد أظهرت النتائج تبعية إدارة العلاقات العامة للإدارة العليا بشكل مباشر، وعدم كفاية عدد الموظفين فيها للقيام بالمهام المسندة إليهم، كما أنّ جميع هؤلاء الموظفين هم من حملة الإجازات الجامعية، إلّا أنّها لا تندرج جميعها ضمن الاختصاصات ذات الصلة بعمل العلاقات العامة، وتعاني هذه الإدارة من نقص في أجهزة الاتصال الضرورية لممارسة أعمالها. وعلى الرغم من أنّ الإدارة العليا تقوم بتخصيص موازنة محددة لإدارة العلاقات العامة، إلّا أنّها لا تغطي حاجاتها بالشكل الكافي فهم يعانون من النقص في الموارد البشرية والمادية. بالإضافة إلى جهل نسبة كبيرة من العاملين في الفندق بطبيعة مهام ووظائف هذه الإدارة، كما لا تستغلّ المنشأة الفندقية بنيتها التحتية الإلكترونية الجيدة بحسب رأي جمهورها الداخلي للتواصل معهم بصورة صحيحة. قدمت الدراسة مجموعةً من التوصيات كان من ضمنها زيادة اهتمام الإدارة العليا في المنشأة الفندقية بإدارة العلاقات العامة، وإنشاء قسم خاص ضمن إدارة العلاقات العامة يعتني بأمور الجمهور الداخلي فقط، مع التركيز على توفير سبل اتصال كافية للتواصل مع الجمهور الخارجي للمنشأة بفاعلية أكبر.